2017
DOI: 10.1021/acsmacrolett.7b00099
|View full text |Cite
|
Sign up to set email alerts
|

Star Architecture Promoting Morphological Transitions during Polymerization-Induced Self-Assembly

Abstract: Polymerization-induced self-assembly (PISA) via reversible addition−fragmentation chain transfer (RAFT) dispersion polymerization is an effective method to produce block copolymer nano-objects of various morphologies at high solids. However, current PISA formulations have been limited to linear block copolymers. We report the synthesis of AB 2 star block copolymers via RAFT aqueous dispersion polymerization of diacetone acrylamide using a poly(ethylene glycol) methyl ether bearing two chain transfer agents as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 38 publications
2
98
0
4
Order By: Relevance
“…In pure water, in particular, there are only a handful of reports beyond diblock copolymers, most of them based on linear block copolymers (triblock or multiblock) and to the best of our knowledge, there is only one example based on a more complex Y‐shape architecture (AB 2 ). This latter structure was formed via RAFT dispersion polymerization of diacetone acrylamide (DAAm) in water using a ω‐bifunctional poly(ethylene glycol) (PEG) macro‐CTA . The authors compared the morphologies obtained with those from a monofunctional macro‐RAFT agent, yielding conventional PEG‐ b ‐PDAAm diblock copolymers, and demonstrated that the Y‐shaped copolymer, PEG‐ b ‐(PDAAm) 2 , promotes the production of nanoobjects with high‐order morphologies through the formation of bulky hydrophobic segments.…”
Section: Introductionmentioning
confidence: 99%
“…In pure water, in particular, there are only a handful of reports beyond diblock copolymers, most of them based on linear block copolymers (triblock or multiblock) and to the best of our knowledge, there is only one example based on a more complex Y‐shape architecture (AB 2 ). This latter structure was formed via RAFT dispersion polymerization of diacetone acrylamide (DAAm) in water using a ω‐bifunctional poly(ethylene glycol) (PEG) macro‐CTA . The authors compared the morphologies obtained with those from a monofunctional macro‐RAFT agent, yielding conventional PEG‐ b ‐PDAAm diblock copolymers, and demonstrated that the Y‐shaped copolymer, PEG‐ b ‐(PDAAm) 2 , promotes the production of nanoobjects with high‐order morphologies through the formation of bulky hydrophobic segments.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,6,7 Another important parameter, that has received much less attention so far in PISA, should be the macromolecular architecture of the polymer chains. Hitherto there are only few reports in the literature comparing notably linear chains with stars or branched structures, 13,14 diblocks with triblocks or multiblocks [15][16][17][18][19][20][21][22] in PISA. Nonetheless, most of the studied systems are currently based on simple AB diblock copolymers, where A is the solvophilic, stabilizer block, and B is the solvophobic block.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, Wang et al. investigated the effect of polymer architecture on the morphology of diblock copolymers synthesized via PISA . A novel difunctional poly(ethylene glycol) (PEG)‐based macro‐CTA was synthesized.…”
Section: Raft Dispersion Polymerizationmentioning
confidence: 99%